Low-carbon effects of farmers’ digital economy participation: further discussing digital equality - Wang, Xinyao; Li, Xinyi (Frontiers in Sustainable Food Systems, 2025)
IntroductionUnder the urgent need to deal with climate change and achieve the dual-carbon goal, integrating the digital economy and traditional agriculture has become an important starting point for promoting the low-carbon agricultural transformation. In the context of the digital economy, it will be more practical to pay attention to the main role of micro-farmers in low-carbon agricultural development.MethodsThis paper uses farmer survey data from 10 provinces in China, including Guangdong, Zhejiang, Shandong, and Heilongjiang, to study the impact and mechanism of digital economy participation on farmers’ low-carbon production performance.ResultsDigital economy participation can significantly improve farmers’ low-carbon production performance. Farmers’ low-carbon production willingness and low-carbon production behavior are important ways for digital economy participation to exert low-carbon effects. Farmers with rural elite status and outworking who participate in the digital economy will actively improve their low-carbon production performance.DiscussionDigital economic inequality will impact the low-carbon effect of farmers’ digital economy participation. This effect is more obvious for farmers with older age and lower education levels.